Blood pressure recovery ratio after exercise test predicts increased carotid intima media thickness in patients with metabolic syndrome (Annals of Medical Research, 2024)
Aim: We aimed to evaluate the relation of BP recovery ratio (BPRR) and carotid intima media thickness (CIMT) in patients with metabolic syndrome. Abnormal blood pressure (BP) recovery after physical exercise is related with coronary artery disease, impaired left ventricular diastolic function and pulse wave velocity.Materials and Methods: Among patients who had negative elective exercise test, 109 patients with metabolic syndrome (MetS) were included (65 males, 44 females; mean age 54.8±8.3 years) in our study. Study population were divided into two groups as low carotid IMT (CIMT≤0.9) and high carotid IMT (>0.9). The BPRR was computed by dividing the third minute systolic BP (SBP) by the peak exercise systolic BP.Results: The BPRR was 0.88 and 0.91 in the low and high carotid IMT group, respectively (p=0.008). Patients in increased carotid IMT group had lower values of septal e′, higher creatinine values and higher rates of statin use (p